Peran Pembiayaan Rahn Emas Dalam mengatasi Permasalahan Likuiditas Bank Syariah di Tengah Kenaikan Harga Emas (Studi Kasus Bank Aceh Syariah Cabang Sisingamangaraja Medan) - Shofiyani, Leni; Nurlaila; Anggraini, Tuti (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the implementation of gold rahn financing and its role in addressing liquidity issues amid rising gold prices at PT Bank Aceh Syariah, Sisingamangaraja Branch, Medan. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation. The findings show that gold rahn financing involves application submission, gold appraisal, contract execution, and fund disbursement using qardh, rahn, and ijarah contracts. This scheme supports bank liquidity through its short-term nature, low risk, and highly liquid gold collateral. Rising gold prices further increase collateral value, financing demand, and fund turnover. Keywords: Gold Rahn Financing; Liquidity; Gold Prices